2021
DOI: 10.1002/rev3.3308
|View full text |Cite
|
Sign up to set email alerts
|

Findings and methodologies about student networks, learning, performance and academic achievement in higher education: A literature review on quantitative studies

Abstract: University student networks are recognised to be linked with student performance. Yet, no literature review seems to address student networks together with student learning or achievement. This paper focuses on the quantitative studies conducted since 2000 that relate to this issue. This literature review highlights five research domains: (1) the links between student and peer performance within face‐to‐face networks; (2) the effects of networks’ components (e.g., centrality) on student learning and achievemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 113 publications
(259 reference statements)
0
4
0
4
Order By: Relevance
“…Liem, et al [51], assert that students who exhibit more efficient learning strategies have an elevated degree of motivation, hence enhancing their capacity to effectively participate in task completion and attain their intended goals. Likewise, students who exhibit a lower level of productivity in their academic endeavors tend to experience challenges in achieving success in their personal and professional lives [52]. The productivity of students in their work is contingent upon their achievements, as these achievements serve as a tangible manifestation of their performance [53,54].…”
Section: Student Achievementmentioning
confidence: 99%
“…Liem, et al [51], assert that students who exhibit more efficient learning strategies have an elevated degree of motivation, hence enhancing their capacity to effectively participate in task completion and attain their intended goals. Likewise, students who exhibit a lower level of productivity in their academic endeavors tend to experience challenges in achieving success in their personal and professional lives [52]. The productivity of students in their work is contingent upon their achievements, as these achievements serve as a tangible manifestation of their performance [53,54].…”
Section: Student Achievementmentioning
confidence: 99%
“…2021;Doolan idr. 2021;Li 2022;Stevanović, Božić in Radović 2021;Zrim Martinjak 2022), kar je lahko glavni vir nezadovoljstva študenta (Mehall 2020;Vignery 2021). Za študenta, ki živi oddaljen od družine in najožjih prijateljev, so lahko povezanosti s študijskimi kolegi njegove najpomembnejše socialne povezave in pomemben vir socialne podpore (Mai, Wu in Huang 2021).…”
Section: Zaključekunclassified
“…Glede na spoznanja o pomenu socialnega povezovanja za vzpostavitev učne skupnosti (Swan 2002), občutek pripadnosti (Picciano 2002), posameznikov študijski proces (Vignery in Laurier 2020), motivacijo za študij (Aguilera-Hermida 2020; Aristovnik idr. 2020; Pandit in Agrawal 2021; Smoyer, O'Brien in Rodriguez-Keyes 2020) in študijsko učinkovitost (Vignery 2021; Vignery in Laurier 2020) je študij v socialni izolaciji med pandemijo covida-19 študenta lahko soočil s številnimi izzivi. Omejitev socialnih interakcij lahko povzroči občutek nepovezanosti, kar lahko rezultira v nižji stopnji udeležbe v študijskem procesu, nižjih dosežkih in celo v opustitvi študija; sprememba študijskega konteksta lahko spremeni študentovo doživljanje interakcij in lastne socialne prisotnosti v razredni skupnosti (Li 2022).…”
Section: Teoretična Izhodiščaunclassified
See 1 more Smart Citation
“…SNA has been used to explore interactions within CL groups and their association with achievement, as well. In a recent literature review, Vignery (2021) concluded that the findings are inconsistent; some studies found that students who are more central in their course’s network (both within and across groups) have better performance in the course (e.g. Williams et al, 2019), whereas others found no such effects (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%